AKTUALISASI KONSEP VASUDHAIVA KUTUMBAKAM DI TENGAH TANTANGAN ERA GLOBALISASI (Studi Kasus SD Fajar Harapan) - I Putu Suyasa Ariputra; I Wayan Purtama Yasa; I Nyoman Sumerta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The era of globalization has implications for life that prioritizes technological sophistication and is materialistic, secularistic, hedonistic, pragmatic, and transactional. The era of globalization provides a lifestyle that separates material life from religious teachings. This raises a problem where the sophistication created by humans is used to fulfill lust simply because it is not based on good behavior and morals. Globalization is one of the elements behind the emergence of the idea of character education as an answer in the midst of many conflict issues. Starting from the thought above, the concept of Vasudhaiva Kutumbaka as one of the values of Hindu local wisdom has a strategic space to develop character education in the community. This conception has a universal meaning that is based on love. The purpose of this paper is to analyze the existence of the concept of Vasudhaiva Kutumbakam in the era of globalization through its actualization so that this concept is not merely a slogan. This study uses qualitative research methods with data collection through observation, interviews, and literature study. Vasudhaiva Kutumbakam: the whole world is one family. Vasudhaiva Kutumbakam suggests five things, namely truth, wisdom, love, peace, and ahimsa. Fajar Harapan Elementary School took the momentum of implementing character education by re-grounding the concept of Vasudhaiva Kutumbakam. The actualization of the Vasudhaiva Kutumbakam concept in the era of globalization at Fajar Harapan Elementary School by internalizing it to students by transforming values into school activities, so that this concept can be actualized in every school member. The pattern of praying together and taking turns according to their respective religions, Christmas programs and breaking the fast together, charity programs, and eating and chatting together during breaks are basically a form of actualization of this concept so that the concept of Vasudhaiva Kutumbakam still has an existence to this day.